Sexual and reproductive healthcare needs of Iranian men: A cross-sectional study - Mojgan Javadnoori; Marjan Hajizadeh; Nahid Javadifar; Mohammad Hossein Haghighizadeh (Shahid Sadoughi University of Medical Sciences, 2018)
Background: The sexual and reproductive health (SRH) needs of men have received little attention in Iran's healthcare system. Developing appropriate strategies to meet men's needs requires careful assessment and recognition of their health needs. Objective: The objective of this study is to assess men's SRH needs and satisfaction with received services. Materials and Methods: This descriptive cross-sectional study was conducted with 1068 adult men aged between 20 and 60 years in Ahvaz in 2014. For obtaining the SRH services needs of men, in addition to the self-reported felt needs, expressed needs and unmet needs, a need assessment was also done using a questionnaire that was developed for the research; its validity and reliability were assessed. Results: The men's perceived, expressed and unmet needs for SRH services were, priority-wise, screening and diagnosis of male genital cancers (63.3%), receiving contraceptive methods (36%), diagnosis, and treatment of male sexual dysfunction (86.9%), respectively. Preventing sexually transmitted disease/AIDS (72.1%), using contraceptives correctly (39.5%), and resisting peer pressure (86.6%) were, respectively, the first felt, expressed, and unmet skills men needed. The results of multivariate logistical regression showed that there was a significant statistical correlation between men's SRH needs and their socio-demographic factors (age, marital/educational status, income) ( p < 0 . 05 ). Conclusion: Iranian men have many unmet SRH needs. Felt and expressed SRH needs were different. Educational and counseling services are as important as clinical services.